KONTRIBUSI KEUANGAN SOSIAL ISLAM UNTUK PEDAGANG ANGKRINGAN - Hamdani Hamdani (Fakultas Ekonomi Bisnis Islam, 2025)
The development of Micro, Small, and Medium Enterprises (MSMEs), particularly angkringan (traditional street food stall) businesses, plays a significant role in supporting Indonesia's national economy. However, limited access to capital, low financial literacy, and inadequate support from Shariabased financing institutions remain major challenges in improving the welfare of small entrepreneurs. This study aims to analyze the contribution of Islamic social finance, including zakat, infaq, sadaqah, and waqf (ZISWAF), in strengthening the economic resilience of angkringan traders through empowerment programs implemented by Islamic social finance institutions, particularly the National Board of Zakat (BAZNAS). This research employed a qualitative approach using a case study design. Data were collected through literature review, field observations, and in-depth interviews with 50 angkringan traders in Ngawi Regency. The data were analyzed descriptively to examine the forms and impacts of Islamic social finance on business empowerment. The findings indicate that Islamic social finance has made a significant contribution to improving the economic capacity of angkringan traders through business capital assistance, the provision of food carts, interest-free financing, and business mentoring. In addition to financial support, business sustainability is also influenced by social capital, which consists of trust, social norms and ethics, and social networks that strengthen customer loyalty and business continuity. The synergy between Islamic social finance and social capital enhances entrepreneurial motivation, sustains business performance, and reinforces the economic resilience of traders' households. Therefore, optimizing the management of ZISWAF funds through integrated Sharia-based MSME empowerment programs is essential for promoting inclusive and sustainable economic development.